QUALITATIVE OVERVIEW FOR HIGH-SPEED DATA-OVER-CABLE COMMUNICATION TO INTRA-VEHICLE NETWORK APPLICATIONS - Torres Gómez, Jorge; Kumar Sharma, Rajesh; Hirtz, Gangolf (Telemática, 2019)
Nowadays, vehicles are becoming smart in their interaction with passengers and the surrounding environment to support complex autonomous operations. These functionalities demand further capacities to connect massive sensors inside the vehicle to allow the processing of collected data. Besides, data-intensive applications such as cameras are also the main part of connected devices inside vehicles. The increasing total number of sensors as well as the data-intensive applications demand a novel use of the wired-bus system inside vehicles. Several approaches have been developed through LIN, CAN, FlexRay, MOST, LVDS and Automotive-Ethernet technologies to support the massive connection of sensors with the increase of available bandwidth. LIN, CAN and FlexRay sup-port communication with limited data-rate. On the other hand, MOST and LVDS and Automotive Ethernet-based solutions implement higher data-rate systems deploying additional infrastructure with increased costs. The current report discusses different approaches by considering OFDM (Orthogonal Frequency-Division Multiplexing) based systems for intra-vehicle communications taking into account the similarities with G.hn standard. This standard supporting home networking describes an OFDM based system over different mediums (PLC, coaxial, Phone Line and Cat-5 cables) whose network topology is nearly similar to intra-vehicle networks. This report provides a discussion on the possibility of using OFDM for intra-vehicle communications based on the G.hn standard. Functionalities regarding the defined topology as well as physical layer block diagram definition are illustrated.